Guru Sebagai Role Model Pendidikan Karakter Anak Usia Dini Perspektif Pendidikan Islam dan Ki Hajar Dewantara - 'Aziz, Hafidh (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2016)
This paper aims to discuss the concept of teachers in building moral values and character of early childhood in the perspective of Islamic Education and Ki Hajar Dewantara, using the library research method with technical content analysis found Several things, that teachers are important factors in early childhood education considering the character the development of their morality which are influenced by external authority themselves. in the Islamic Education Perspective that puts the teachers in the respectable position and has a very important role in education, and in view of ki Hajar Dewantara stating that teachers should be able to be an example and role model, a companion and motivator for the students